Introduction To Digital Marketing In Smes In Kampung Baru Village - Dwi Izagi; Pristiyono Pristiyono; Yudi Prayoga (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Technological developments in this day and age are growing very rapidly, this affects small and medium enterprises (SMEs), because inevitably small and medium enterprises (SMEs) must follow the developments of the times otherwise they will be left behind. SMEs as one type of business that plays an important role in increasing the economic growth of a country, requires an appropriate marketing strategy so that products can be sold in the market. Digital marketing is the marketing of products or services through digital media and the internet. Digital marketing is a solution for SMEs in this technological era. The problem faced by SMEs in the village of Kampung Baru Depan is the lack of knowledge about Digital Marketing. This service activity aims to introduce Digital Marketing to SMEs in the village of Kampung Baru Kontak. with the lecture, discussion and question and answer method. The service provider provides material about Digital Marketing, marketing strategies and steps to start Digital Marketing for SMEs in the village of Kampung Baru Promise. The results of this service activity are SMEs in the village of New Promise, which previously used only conventional marketing methods, through this service activity, they could find out another method, namely digital marketing (Digital Marketing) and also practice it directly.